IMPLICATIONS OF ADOLESCENT AND PARENT PERCIEVED SKILL-BUILDING ON MISCARREID HELPING AND SELF-EFFICACY FOLLOWING A TRANSITION WORKSHOP FOR ADOLESCENTS WITH INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Waschmann, Malika; Lin, Henry; Stellway, Jacklyn
Abstract: BACKGROUND: The rising prevalence of Inflammatory Bowel Disease (IBD) in children and subsequent need for continued care into adulthood, begets the call for patient education on the transition to adult healthcare. To address this need, we designed a virtual, transition program for adolescents with IBD and their parents. The objective of this study was to assess program efficacy by examining changes in transition readiness skills, self-efficacy, and miscarried helping. METHODS: Sixteen adolescent-parent dyads participated in the transition workshop. The program was structured around the biopsychosocial model of health and a multidisciplinary group of professionals contributed. The impact of the workshop was measured by validated self- and parent-report measures of transition readiness (transition readiness assessment questionnaire; TRAQ), self-efficacy (IBD-self efficacy scale; IBD-SES), and miscarried helping (Helping for Health Inventory; HHI) at pre-workshop and 1-year post-workshop. Median values were used to perform Wilcoxon rank sum tests and Spearman correlations for statistical analysis. RESULTS: Adolescents gained tangible transition readiness skills as demonstrated by improvement in self- and parent-reported TRAQ scores at 12 months (median increase of 14 points and 19 points respectively, p<0.05). Parents reported less miscarried helping as demonstrated by improved HHI scores, however, adolescents did not (median decrease of 2 points). Adolescent IBD-SES scores improved at 12 months (median increase of 1 point). There was weak correlation between: 1) Adolescent IBD-SES and TRAQ scores (r=0.42), and 2) Parent TRAQ and HHI scores (r=0.49). DISCUSSION/CONCLUSIONS: Improvements in adolescent TRAQ scores indicate that following the workshop, participants more frequently performed tasks necessary to manage their disease. Improvement in parent-reported TRAQ scores suggest parents also witnessed their child taking on more responsibility and developing autonomy. Correlation between improved parent-reported TRAQ scores and improved HHI scores suggests that as adolescents gain more autonomy over the day-to-day tasks of managing their IBD, their parents more readily allow them to take the lead, but the weak correlation observed could be from the small sample size given the attrition in survey response rate at 12 months. The correlation between increased adolescent TRAQ scores and IBD-SES scores suggest that as adolescents engage in disease management tasks they develop increased self-efficacy in relation to their disease as a delayed measure of program success. Future directions include implementing more frequent topic-based workshops to allow for peer-to-peer learning and increasing our sample size to increase the power of our analysis.